2017
DOI: 10.1186/s13756-017-0262-4
|View full text |Cite
|
Sign up to set email alerts
|

Clonal diversity and detection of carbapenem resistance encoding genes among multidrug-resistant Acinetobacter baumannii isolates recovered from patients and environment in two intensive care units in a Moroccan hospital

Abstract: BackgroundCarbapenem-resistant Acinetobacter baumannii has recently been defined by the World Health Organization as a critical pathogen. The aim of this study was to compare clonal diversity and carbapenemase-encoding genes of A. baumannii isolates collected from colonized or infected patients and hospital environment in two intensive care units (ICUs) in Morocco.MethodsThe patient and environmental sampling was carried out in the medical and surgical ICUs of Mohammed V Military teaching hospital from March t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 38 publications
8
22
0
1
Order By: Relevance
“…PFGE typing showed 8 different PFGE cluster (A, B, C, D, E, F, G, and H) with two major cluster A and G with 21 (30.4%) and 6 (23.2%) members, respectively, which contains up to 53.6% of all isolates. In our study, a close genetic relationship between clinical and environmental isolates of A. baumannii was observed that is consistent with other studies [4,21]. These results indicate that the hospital environment is frequently colonized by different A. baumannii clones, which may be responsible for the transmission of A. baumannii isolates between patients and their surroundings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…PFGE typing showed 8 different PFGE cluster (A, B, C, D, E, F, G, and H) with two major cluster A and G with 21 (30.4%) and 6 (23.2%) members, respectively, which contains up to 53.6% of all isolates. In our study, a close genetic relationship between clinical and environmental isolates of A. baumannii was observed that is consistent with other studies [4,21]. These results indicate that the hospital environment is frequently colonized by different A. baumannii clones, which may be responsible for the transmission of A. baumannii isolates between patients and their surroundings.…”
Section: Discussionsupporting
confidence: 92%
“…Of the 41 XDR A. baumannii strains isolated from patients' respiratory tracts, the bacteria isolated from tracheal aspirate specimens were the most common respiratory isolates, which is consistent with previous studies [19,20]. Consistent with the earlier study, the resistance rate of clinical and environmental isolates of A. baumannii to antibiotics was 95-100% and there was no significant difference between antibiotic resistance in clinical and environmental isolates (p > 0.05) [21]. One of the important features related to the virulence of A. baumannii is its ability to form biofilms.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study by Mody et al [40] demonstrated that contamination of patients' hands with MDRO is frequent and correlates with contamination of high-touch surfaces. Patients who were colonized or infected with CRAB were also shown to have higher environmental contamination with clonal CRAB compared to patients who were not [39,41]. The higher burden of MDRGN as usually observed in clinical infections, has been shown to increase environmental contamination [42,43].…”
Section: Non-outbreak Reportsmentioning
confidence: 99%
“…Studies have demonstrated MDRGN contaminating dry surfaces in the hospital environment can also be responsible for the spread of infection [41]. HCWs responsible for cleaning and decontamination should be educated and monitored for strict adherence to protocols for decontamination of environment where patients infected/ colonized with MDRO are housed.…”
Section: Summary Of Evidence and Future Researchmentioning
confidence: 99%
“…Moreover, Mohammadi et al reported similar results among hospitalized patients with burn infection in 2016 in Iran [32]. Therefore, it is not surprising that Chen et al in 2017 in China, Uwingabiye et al in 2017 in Morocco, and Nowak et al in 2017 in Greece, Italy, and Spain reported similar results in their investigations [33], [34], [35]. The percentage of bla OXA-24-like genes, which encode acquired carbapenemases, was 93.6% in the present study, followed by bla OXA-40-like with 48.9%.…”
Section: Discussionmentioning
confidence: 75%